Effect of β-HYDROXY- β-methylbutyrate (HMB) supplementation on the body-composition and muscle power output on non competitive sporting males between 19 and 24 years who performed resistance training three times a week for 8 weeks - Du Toit, Peet J. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.